2013
DOI: 10.1080/10426507.2012.744014
|View full text |Cite
|
Sign up to set email alerts
|

Amidoalkylating Properties of 1-(N-Acylamino)Alkyltriphenylphosphonium Salts

Abstract: Easily accessible 1-(N-acylamino)alkyltriphenylphosphonium salts react smoothly with nitrogen, sulfur, phosphorus and oxygen nucleophiles in the presence of (i-Pr) 2 EtN to give the expected α-amidoalkylation products, usually in good or very good yields. α-Amidoalkylation of dialkyl malonates or acetylacetates requires the application of a much stronger base (DBU) and gives the best results under the influence of microwave irradiation. α-Amidoalkylation of enamines was carried out successfully in the presence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 23 publications
0
19
0
Order By: Relevance
“…The N-acylated -aminoalkylphosphonic and -aminoalkylphosphinic acids esters used in this work were prepared as racemic mixtures using the method described in our previous papers [21][22][23][24] (Table 1). Their hydrolysis in 2 M hydrochloric acid to N-acylated acids was satisfactorily performed according to a well-known method [42] (Scheme 1, Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The N-acylated -aminoalkylphosphonic and -aminoalkylphosphinic acids esters used in this work were prepared as racemic mixtures using the method described in our previous papers [21][22][23][24] (Table 1). Their hydrolysis in 2 M hydrochloric acid to N-acylated acids was satisfactorily performed according to a well-known method [42] (Scheme 1, Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we have developed a new, effective two-stage method for the transformation of N-acyl-α-amino acids into their phosphonic or phosphinic analogues via the electrochemical decarboxylative α-methoxylation of N-acyl-α-amino acids to N- (1-methoxyalkyl)amides and the Michaelis-Arbuzov-type amidoalkylation of the proper phosphorus nucleophile with the latter compounds [21][22][23][24]. The method enables easy access to a variety of N-acylated -aminoalkylphosphonic and -aminoalkylphosphinic acid esters of diversified structure, including the most interesting group of these compounds with the substituents at the -position identical with those ones characteristic for natural, -amino acids, both proteinogenic and unproteinogenic.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the recently described protocol [8], we have demonstrated that 1-( N -acylamino)alkyltriarylphosphonium salts 4 with weakened C α -P + bond strength react with 1-morpholinocyclohexene in Stork-type enamination to give the expected products 8 with good yields. We have proved that this reaction can be conducted in acetonitrile, at room temperature and without using any base catalysts.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of a positively charged nucleofugal phosphonium moiety in the close surroundings of the N -acyl group determines its unique chemical properties such as high reactivity in α-amidoalkylations [1,2,3,4,5,6,7,8,9,10]. This type of reactions has enjoyed unflagging interest for years as a synthetic method with great potential, especially valuable for C-C and C-heteroatom bond formation [1,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation